2002
DOI: 10.1046/j.1440-169x.2002.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Conserved expression control and shared activity between cognate T‐box genes Tbx2 and Tbx3 in connection with Sonic hedgehog signaling during Xenopus eye development

Abstract: Tbx2 and Tbx3 are considered to be cognate genes within a Tbx2/3/4/5 subfamily of T-box genes and are expressed in closely overlapping areas in a variety of tissues, including the eye. Herein, we show that misexpression of Tbx2 and Tbx3 in Xenopus embryos gave rise to defective eye morphogenesis, which was reminiscent of the defect caused by attenuated Sonic hedgehog (Shh) signaling. Indeed, Tbx2/3 misexpression suppressed Gli1, Gli2, Ptc2 and Pax2, mediators or targets of Hedgehog (Hh) signals. From these dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 70 publications
3
37
0
Order By: Relevance
“…Xtbx6r-VP16 and Ztbx24 induce tail-like structures when overexpressed in the animal region. This phenomenon has also been observed in injection experiments involving Xbra (Tada-et al, 1997), Xtbx6 (Yabe, data not shown), or Xtbx2/3-VP16 (Takabatake et al, 2002), suggesting that this activity is common to transcriptional activator-type T-box genes. These results also indicate that Xtbx6r and Ztbx24 have quite opposite effects, suggesting that Xtbx6r is not an ortholog of Ztbx24.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Xtbx6r-VP16 and Ztbx24 induce tail-like structures when overexpressed in the animal region. This phenomenon has also been observed in injection experiments involving Xbra (Tada-et al, 1997), Xtbx6 (Yabe, data not shown), or Xtbx2/3-VP16 (Takabatake et al, 2002), suggesting that this activity is common to transcriptional activator-type T-box genes. These results also indicate that Xtbx6r and Ztbx24 have quite opposite effects, suggesting that Xtbx6r is not an ortholog of Ztbx24.…”
Section: Discussionsupporting
confidence: 62%
“…Xtbx2 and Xtbx3/ET are first expressed in the anterior neural plate and become localized later in the dorsal retina of the tadpole (Li et al, 1997;Hayata et al, 1999). Overexpression of these genes in the eye field causes defects in the ventral retina (Takabatake et al, 2002). Eomesodermin is first expressed in the dorsal mesoderm, but also expressed later in the telencephalon of the tadpole and is suggested to be involved in neural differentiation (Ryan et al, 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…The following primers were used: xMID1, 5Ј-GTTGTCTTCTCTGTTGAATAA-3Ј and 5Ј-TGTATAATGGT TCT -GTTTGAT-3Ј; xMID2, 5Ј-GTCATGAAGTTAAGAAAACTTGCTC-3Ј and 5Ј-ACCTTCAAGCAATTTCTTCTCTCTG-3Ј; NCAM, 5Ј-GCCT G -TAGAATTACAATGCTG-3Ј and 5Ј-AGCATCTTGGCT GCTGGCATT-3Ј; Sox2, 5Ј-GAGGATGGACACTTATGCCCAC-3Ј and 5Ј-GGACATGC -TGTAGGTAGGCGA-3Ј; Epidermal keratin I, 5Ј-CGGTTGAAGG -TAACCTGA-3Ј and 5Ј-CAACCTTCCCATCAACCA-3Ј; ODC, 5Ј-CAG -CTAGCTGTGGTGTGG-3Ј and 5Ј-CAACATGGAA ACTCACACC-3Ј. The following plasmids were used for probe synthesis: xMID1 and xMID2 (constructed for this study); Sox2 (XL039o24, XDB3); NCAM (Kintner and Melton, 1987); N-cadherin (XL289n05ex, XDB3); Epidermal keratin I (XL056e18, XDB3); Shh (Yakushiji et al, 2007); Ptc2 (Yakushiji et al, 2007); Gli1 (Takabatake et al, 2000); Gli3 (Takabatake et al, 2000); HNF3 (FoxA2a) (XL016l12, XDB3); Pintallavis (FoxA4a) (XL047n03, XDB3); N-tubulin (Takabatake et al, 2002); Shroom3 (Haigo et al, 2003); and Pax3 (XL014p10, XDB3).…”
Section: Rt-pcr and In Situ Hybridizationmentioning
confidence: 99%
“…ET/Tbx3, a T-box protein involved in the block of Rx1 transcriptional activity, is expressed in eye and cement gland primordia (Zuber et al, 2003). Moreover, both Six3 and ET are involved in Sonic hedgehog (Shh) signaling activity during the formation of the two bilateral eye fields from the initially single one (Takabatake et al, 2002;Geng et al, 2008). Lhx2, a LIM-homeodomain protein, is recruited in EFTFs transcriptional complexes, but it is involved in later events such as optic cup and lens formation (Yun et al, 2009).…”
Section: Initial Specification Of Retinal Fate: the Eye Fieldmentioning
confidence: 99%